Correction of musculoskeletal disorders in students of special medical health group ‘a’ through swimming and water-based muscle strengthening exercises - Romanchenko, S.A.; Grigan, S.A. (Theory and Practice of Physical Culture, 2026)
Musculoskeletal disorders in students are considered one of the most common forms of functional deviations in young age. The majority of students exhibit various forms of posture disorders, including scoliotic posture, increased physiological spinal curvatures, asymmetry of the shoulder girdle and pelvis. Students of special medical group ‘A’ represent a contingent with functional deviations that do not impede physical education classes but require adaptation of the content and intensity of the load. The main objectives of physical education for this group are the correction of identified deviations, restoration of the functional state of the musculoskeletal system (MSS), and the formation of stable self-control skills. Objective of the study is to scientifically substantiate and experimentally verify the effectiveness of a comprehensive program for correcting functional musculoskeletal disorders in students of special medical health group ‘A,’ based on the combined use of swimming and exercises aimed at strengthening the muscular corset, within the process of physical education in a higher educational institution. Methods and structure of the study. The study was conducted at DSTU from September to December during physical education classes for students of special medical group ‘A.’ Results and conclusions. The research results confirm the advisability of a comprehensive approach to organizing classes for students of special medical health group ‘A,’ wherein swimming and muscle-strengthening exercises are considered not as auxiliary, but as fundamental components of correctional and health-improving work.